Localized light chain amyloidosis: A self-limited plasmacytic B-cell lymphoproliferative disorder - Martínez, José C.; Lichtman, Eben I. (Frontiers in Oncology, 2022)
Immunoglobulin light chain amyloidosis can be either systemic or localized. Although these conditions share a similar name, they are strikingly different. Localized light chain amyloidosis has been challenging to characterize due to its lower incidence and highly heterogeneous clinical presentation. Here, we review the emerging literature, emphasizing recent reports on large cohorts of patients with localized amyloidosis, and provide insights into this condition's pathology and natural history. We find that patients with localized amyloidosis have an excellent prognosis with overall survival similar to that of the general population. Furthermore, the risk of progression to systemic disease is low and likely represents initial mischaracterization as localized disease. Therefore, we argue for the incorporation of more sensitive techniques to rule out systemic disease at diagnosis. Finally, despite increasing mechanistic understanding, much remains unknown regarding the origins of the cells and molecular processes that give rise to amyloid formation in this condition.